Spintronic Logic Circuits for Ultrafast Processing - Vaibhav Godase; Shilpa Shinde (International Journal of VLSI Circuit Design & Technology, 2025)
Spintronic logic has emerged as one of the most promising post-CMOS paradigms capable of addressing the speed, density, and energy challenges of deeply scaled silicon technologies. By relying on the intrinsic properties of electron spin and magnetization dynamics, spintronic devices—particularly Magnetic Tunnel Junctions (MTJs), Spin-Transfer Torque (STT), and Spin–Orbit Torque (SOT) structures—enable ultrafast, non-volatile data processing with significantly reduced energy consumption. Despite remarkable device-level advancements, circuit- level realization of high-speed, low-energy spintronic logic remains underdeveloped due to switching delay constraints, inefficient spin injection, and the difficulty of hybrid CMOS–spin integration. This paper proposes a comprehensive device-to-circuit framework for modeling, designing, and evaluating spintronic logic circuits aimed at ultrafast computation. Using a hybrid simulation flow combining micro magnetic modeling and SPICE-based circuit analysis, we design optimized inverter, majority gate, XOR/XNOR, and full-adder circuits that exploit majority-based logic inherent in spintronic devices. Results demonstrate that spintronic logic circuits can achieve up to 65–80% reduction in energy per operation, 3× improvement in non-volatility-driven retention, and delay improvements of 30–45% compared to 7 nm CMOS equivalents under specific write conditions. The circuits show strong potential for arithmetic processing, cryptographic computation, and neuromorphic in-memory logic fabrics. The proposed architecture contributes a scalable, robust pathway for integrating spintronic logic into next-generation ultrafast computing systems, and provides a foundation for developing high- performance SOT-based processors, probabilistic spin logic accelerators, and 3D spin-memory computing arrays.
Keywords: Magnetic Tunnel Junction; Majority Gate Logic; Spin-Transfer Torque; Spintronics; Spin–Orbit Torque; Ultrafast Logic